Adaptive Curriculum Development in Preparing Future Generations for 21st Century Challenges - Slamet Gunawan; Ma’mun Hanif; Putri Dyah Ayu Rosalinda; Nailatul Karomah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2026)
Curriculum development is a dynamic process that can be carried out at any time in response to the needs of the educational world. In facing the challenges of the 21st century—marked by rapid technological advancements, globalization, and increasing social complexity—curricula are required to be more adaptive and relevant. This study aims to analyze changes in curriculum objectives, the development of instructional materials and teaching methods, and the transformation of assessment systems. This study employed a literature review method using a qualitative descriptive approach. The data sources consisted of books, scientific journals, and official documents related to curriculum development and 21st-century education published between 2002 and 2024. A total of 20 relevant literature sources were analyzed using thematic analysis and data synthesis techniques to identify key patterns, concepts, and findings related to curriculum development. The findings indicate that the curriculum must focus on strengthening 21st-century skills, including critical thinking, creativity, communication, and collaboration, as well as the integration of technology into the learning process. Additionally, the assessment system needs to be developed more comprehensively through the implementation of authentic assessment that encompasses cognitive, affective, and psychomotor aspects. Thus, curriculum development is expected to produce students who are not only academically excellent but also possess the skills and character required to face future challenges